Nigerian family physicians' knowledge of oral diseases and their attitude to oral health care - a pilot study - O. O. Sofola; O. O. Ayankogbe (Nigerian Dental Association, 2009)
Objective: Access to oral health care in most developing countries is poor and physicians may be in a better position to facilitate early detection and prompt referrals for oral diseases in such populations. The objective of this study was to assess the oral health knowledge of family physicians in Lagos, Nigeria and to determine their attitudes to oral health care. Method: The study was a cross-sectional, self administered questionnaire survey of family health practitioners in fifty randomly selected private hospitals in Lagos metropolis. The questionnaire assessed knowledge on the aetiology and prevention of dental caries and periodontal diseases as well as oral health related behaviour of the physicians. Result: Eighty-one questionnaires were returned properly filled. Forty-two (51.9%) respondents had ever experienced dental treatments. Nearly all (95.1%) respondents had been consulted by their patients for dental problems. Oral health knowledge was not satisfactory with 54% and 45.7% of them being able to give a correct description of dental caries and periodontal diseases respectively. Physicians who had practiced for ten years or less had better knowledge than those who had practiced for over fifteen years. This was however not statistically significant. Findings also revealed misconceptions about the aetiology of these diseases. Conclusion: Oral health should be included in update courses for medical doctors especially those designated as primary health care providers. Training curriculum of family medicine practitioners should be expanded to include oral health education.